Electrospinning polymer blend of PLA and PBAT: Electrospinnability–solubility map and effect of polymer solution parameters toward application as antibiotic‐carrier mats. Issue 28 (30th March 2018) - Khatsee, Sarunphat; Daranarong, Donraporn; Punyodom, Winita; Worajittiphon, Patnarin
ABSTRACT: Electrospinning of a biodegradable polymer blend of poly(lactic acid) (PLA) and poly(butylene adipate‐ co ‐terephthalate) (PBAT) is reported for the first time. Effects of several solution parameters on electrospinning are explored, including types of single and binary solvents, binary solvent mixing ratio, polymer blend concentration, polymer blending ratio, and loading content of tetrabutyl titanate as a compatibilizer. An electrospinnability–solubility map of the PLA/PBAT blend is firstly developed for the facile selection of a suitable binary solvent system, thus simplifying the laborious, time‐consuming, trial‐and‐error process. A particular binary solvent system derived from good and non‐solvent serves as the most suitable medium for the successful preparation of homogeneous bead‐free electrospun PLA/PBAT nanofibers. It is revealed that the compatibilizer acts not only as a diameter size tuner for the PLA/PBAT fibers but also as a mechanical property enhancer for the immiscible PLA/PBAT electrospun mats. Moreover, the antibacterial activity of the drug‐loaded PLA/PBAT fibrous mats suggests their potential application as antibiotic‐carrier mats. Preparation of the composite mats comprising bead‐free fibers with an average size at sub‐micrometer scale is also demonstrated, additionally promoting the possibility of using the PLA/PBAT‐based electrospun mats as a matrix of various additives for a wide range of applications. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46486. Abstract :